2016
DOI: 10.1016/j.elecom.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Si-based anodes for Ca-ion batteries: Electrochemical decalciation of CaSi2

Abstract: Density Functional Theory (DFT) calculations are used to investigate basic electrochemical characteristics of Si-based anodes in Calcium Ion Batteries (CIBs). The calculated average voltage of Ca alloying with fcc-Si to form the intermetallic Ca x Si phases (0.5 < x ≤2) is of 0.4V, with a volume variation of 306%. Decalciation of the lower Ca content phase, CaSi 2, is predicted at an average voltage between 0.57 V (formation of Si-fcc, 65% volume variation) and 1.2 V (formation of metastable deinserted-Si phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 16 publications
0
44
0
Order By: Relevance
“…Attractive electrochemical capacities may also be possible using alloy‐based anode materials. Ponrouch et al investigated the feasibility of using Ca–Si intermetallic alloys as anodes for CIBs with an attractive maximum theoretical capacity of 991 mAh g −1 for the reaction of 1 mol fcc–Si with 2 mol of Ca ions. As a first step in the examination of the feasibility of Ca–Si alloy anodes they investigated the commercially available Ca–Si alloy CaSi 2 .…”
Section: Anodes For Nonaqueous Ca‐ion Batteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Attractive electrochemical capacities may also be possible using alloy‐based anode materials. Ponrouch et al investigated the feasibility of using Ca–Si intermetallic alloys as anodes for CIBs with an attractive maximum theoretical capacity of 991 mAh g −1 for the reaction of 1 mol fcc–Si with 2 mol of Ca ions. As a first step in the examination of the feasibility of Ca–Si alloy anodes they investigated the commercially available Ca–Si alloy CaSi 2 .…”
Section: Anodes For Nonaqueous Ca‐ion Batteriesmentioning
confidence: 99%
“…Nanostructuring and Temperature Elevation : Two further ways of improving the performance of multivalent ion insertion electrodes are the use of nanostructured materials to reduce the diffusion length from the electrode surface into the bulk[6b,41] and the elevation of the cell operating temperature. The use of elevated temperature cycling proved essential to the demonstration of reversible magnesium cycling in TiS 2 and thiospinels[23a] and also in the demonstration of reversible Ca plating in conventional electrolytes . However, the increased temperature of cell operation unfortunately also increases the kinetics of parasitic side reactions such as current collector corrosion and electrolyte breakdown …”
Section: Cathodes For Calcium‐ion Batteriesmentioning
confidence: 99%
“…Using a Sn anode and graphite cathode, Wang et al [14] recently reported a highvoltage (4.45 V) CIB cell with a reasonable capacity of 85 mAh g and a remarkable cyclability (95% capacity retention in 350 cycles). [13,14,30,31] All of them except Na have been reported to mix with Ca in wide composition ranges, forming various intermetallic compounds. [13,14,30,31] All of them except Na have been reported to mix with Ca in wide composition ranges, forming various intermetallic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Using a Sn anode and graphite cathode, Wang et al recently reported a high‐voltage (4.45 V) CIB cell with a reasonable capacity of 85 mAh g and a remarkable cyclability (95% capacity retention in 350 cycles). Besides Sn, several metals and metalloids including Zn, Al, Si, Li, and Na have also been investigated for the use of alloying‐type CIBs anodes with largely disparate capacities achieved . All of them except Na have been reported to mix with Ca in wide composition ranges, forming various intermetallic compounds .…”
Section: Introductionmentioning
confidence: 99%
“…First principles calculations are a unique tool to accelerate the identification of materials which could sustain reversible intercalation reactions delivering high specific energy [9][10][11][12][13] . A recent computational investigation of spinel AM 2 as a potential electrode material for Ca ion batteries 14 .…”
mentioning
confidence: 99%